New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil - Ochoa, Luz E. [UNESP]; Silva, Gabriel S.C. [UNESP]; Silva, Guilherme J. Costa E. [UNESP]; Oliveira, Claudio [UNESP]; Datovo, Alessio (Magnolia Press, 2017)
A new species of trichomycterid catfish, Trichomycterus pascuali, is described from Paranapanema basin and is distin-guished from all congeners by the possession of five pectoral-fin rays and the absence of pelvic fin, girdle, and muscles. Additional features further differentiate the new species from the other congeners lacking pelvic fins, T. candidus, T. catamarcensis, and T. tropeiro. The identification of T. pascuali is additionally corroborated by genetic divergence based on DNA-barcode analysis. Osteological and myological data unequivocally support the inclusion of the new species in the Trichomycterinae and molecular analyses justify its allocation to the genus Trichomycterus rather than Eremophilus, a trichomycterine taxon traditionally diagnosed by the lack of pelvic fins. Our genetic analysis further indicates that pelvic fins were independently lost in E. mutisii, T. candidus, and T. pascuali.
Keywords: Freshwater catfish; Pelvic-fin loss; Taxonomy; Upper Paraná Basin